Inter-Actor Coordination Challenges in Community-Based Mental Health Services: Tantangan Koordinasi Antar-Pihak dalam Layanan Kesehatan Mental Berbasis Masyarakat - Annisha Dini Koernea; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Community-based mental health services are central to achieving inclusive and sustainable public health goals, particularly in rural settings. Specific Background: In Indonesia, the Posyandu Jiwa program serves as a village-level mechanism to provide integrated mental health care through collaboration among health workers, village governments, cadres, and families. Knowledge Gap: Existing studies rarely examine how coordination among multiple local actors shapes the practical implementation of Posyandu Jiwa at the village level. Aims: This study aims to analyze coordination among actors in the implementation of the Posyandu Jiwa program in Kalitengah Village, Sidoarjo Regency. Results: The findings reveal that coordination structures formally exist; however, limitations persist in program integration, clarity of communication, division of roles, and discipline, particularly due to cadre role overlap and family resistance to treatment. Novelty: This study provides an in-depth, actor-centered analysis of coordination dimensions within a village-based mental health service context. Implications: Strengthening inter-actor coordination and fostering active family participation are essential for sustaining community-based mental health programs and improving service continuity.